21. Generators of oddball P300 to visual omitted stimuli: A simultaneous EEG-fMRI study. Issue 4 (April 2016) - Di Rollo, A.; Cosottini, M.; Pesaresi, I.; Fabbri, S.; Barloscio, D.; Ragazzoni, A.; Sartucci, F.
Abstract : The present study aimed at investigating the cerebral sources of the visual P300 event-related potential (ERP) by the simultaneous recording of EEG and functional magnetic resonance imaging (fMRI). In addition to a standard two-stimuli visual "oddball" paradigm we applied a similar paradigm, in which the rare (target) stimuli were omitted in a sequence of regularly presented visual stimuli. Both conditions were preceded by a trial in which the subject gave no attention to the stimuli (passive condition). The EEG showed a clear N1/P3 complex during the standard "oddball" paradigm, whereas during the "omitted stimulus oddball" only a P300 component, with reduced amplitude and increased latency (about 700 msec, compared to 400 msec in the standard paradigm) was observed. fMRI showed, during the standard "oddball", activations in lateral frontal, fronto- operculum, anterior insula regions, prevailing on the right. Minor activations were observed bilaterally in the parietal cortex near the intraparietal sulcus and in posterior temporal regions, also more evident on the right hemisphere. The "omitted stimuli" paradigm showed fMRI activations in the very same locations as those obtained in the standard "oddball". These results highlight the "real" cortical sources of the endogenous P300, not contaminated by sensory activations.